(untitled) - Harris, Thomas (New York, 1999)
Michael Lander is the most dangerous man in America. He pilots a television blimp over packed football stadiums every weekend. He is fascinated with explosives...
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy